Burt Rutan, Cal Poly alumnus
Aeronautical engineering alumnus Burt Rutan is a gifted engineer, designer, and entrepreneur. His company, Scaled Composites, has designed over 40 new airplanes since 1972, including the record-breaking Voyager, the first airplane to circle the world non-stop without refueling. Today Voyager hangs in the Smithsonian Institution's National Air and Space Museum in Washington D.C.